Relationships between heart rate variability and indirect indicators of hydration status in elite male field hockey players - Vescovi, J. D.; Mandic, I.; Watson, G. (International Journal of Sports Science & Coaching, 2022)
The aim of this study was to examine the relationship between resting morning heart rate variability (HRV) metrics and indirect markers of hydration status in elite male athletes. Twenty-two field hockey players (age 26.8 ± 3.4 yr; height 178.4 ± 6.3 cm; body mass 76.2 ± 7.4 kg) were monitored over 10-d during a pre-Olympic training camp. Measurement of heart rate variability (HRV) during an orthostatic challenge, urine specific gravity (Usg, first morning void) and body mass were captured on seven of the mornings. Individual generalized linear mixed models evaluated the relationships between supine and standing HRV metrics with Usg and day-to-day change in body mass. No meaningful relationships were identified between supine (estimates -0.002 to 0.001) or standing (-0.002 to 0.003) HRV metrics and Usg as well as between supine (-0.003 to 0.016) or standing (-0.004 to 0.006) HRV metrics and changes in body mass. These outcomes indicate that supine and standing HRV metrics are not influenced by indirect indices of hydration status in elite male field hockey players.